The Influence Of Tourist Attraction On Visit Decision Through Visitor Experience At Taman Mini Indonesia, Jakarta - Filma Festivalia; Rina Suprina; Gratia Wirata Laksmi; Mochamad Achmadi; Wijayanti Dewi Prabandari (Journal of Business on Hospitality and Tourism, 2025)
This study examines the factors influencing the decision to visit Taman Mini Indonesia Indah (TMII), Jakarta, focusing on the roles of tourist attraction, visitor experience, and their impact on visit decision. Understanding these dynamics is crucial for improving the destination's appeal and enhancing visitor satisfaction. The research employed a quantitative approach using surveys from visitors to collect data, with SmartPLS used for data analysis. The results show that tourist attraction directly affects the decision to visit and also exerts an indirect effect through visitor experience, which acts as a mediator. These findings emphasize the importance of improving visitor experiences to influence future visit intentions. The study contributes to tourism management by highlighting key factors that influence visitor decision-making and provides practical insights for destination marketing. Future research could explore broader contexts and the impact of digital engagement on visitor decisions.